2022
DOI: 10.3390/tomography8010012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cardiopulmonary Interactions and Exploring Their Prognostic Value in Acute Bronchiolitis: A Prospective Cardiopulmonary Ultrasound Study

Abstract: We aimed to delineate cardiopulmonary interactions in acute bronchiolitis and to evaluate the capacity of a combined cardiopulmonary ultrasonography to predict the need for respiratory support. This was a prospective observational single-center study that includes infants <12 month of age admitted to a hospital due to acute bronchiolitis. All the included patients underwent clinical, laboratory and cardiopulmonary ultrasonographic evaluation at the same time point within 24 h of hospital admission. The exis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 42 publications
4
6
1
Order By: Relevance
“…A growing body of evidence shows the applicability and benefits of noninvasive complementary exams such as cardiopulmonary ultrasound to evaluate the severity of acute bronchiolitis 38–40 . Our findings suggest that urinary NT‐proBNP measurements could be another useful noninvasive tool, overall, in settings where ultrasound expertise is not available.…”
Section: Discussionmentioning
confidence: 81%
“…A growing body of evidence shows the applicability and benefits of noninvasive complementary exams such as cardiopulmonary ultrasound to evaluate the severity of acute bronchiolitis 38–40 . Our findings suggest that urinary NT‐proBNP measurements could be another useful noninvasive tool, overall, in settings where ultrasound expertise is not available.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, it is not surprising that urine NT-proBNP presented similar results for clinical outcomes of severity in acute bronchiolitis than those previously reported for serum NT-proBNP, pointing out the potential value of the measurement of urinary NT-proBNP as a non-invasive tool to assess severity in acute bronchiolitis. A growing body of evidence shows the applicability and benefits of non-invasive complementary exams such as cardiopulmonary ultrasound to evaluate the severity of acute bronchiolitis in previously healthy infants [32][33][34]. Our findings suggest that urinary NT-proBNP measurements may be another useful non-invasive tool for this, overall, in settings where ultrasound expertise is not available.…”
Section: Association Of Urine Nt-probnp With Severitymentioning
confidence: 78%
“…The proposal of LUS provides quantitative indicators for clinical practice, which could reflect the more comprehensive and systematic nature and severity of lung lesions. Rodriguez et al 22 found that the higher LUS ( p < 0.001) increased the Tei index ( p < 0.001) and pulmonary artery pressures ( p < 0.001), and that is a positive correlation between LUS and additional ventilation mode classification and ventilator use time. In this study, LUS was also positively associated with pulmonary arterial pressure, assisted breathing therapy, and days of invasive mechanical ventilation, which supports the literature view.…”
Section: Discussionmentioning
confidence: 97%